Ways of combatting the high infant mortality rate in Turkey - Asvall, Jo E. (The Turkish Journal of Pediatrics, 1986)
The author, during a lecture given to the XXXth Congress of the Turkish National Pediatric Society in March 1986 in Ankara, discusses the high infant mortality rate in Turkey and the public health as well as perinatal measures which need to be taken in order to bring this statistic into line with the rest of the European region.
Keywords: infant mortality; Turkey